SAT0436 Abatacept in the Treatment of Adult Dermatomyositis and Polymyositis: Artemis, a Randomized, Treatment Delayed-Start Trial. (9th June 2015) - Tjärnlund, A.; Dastmalchi, M.; Mann, H.; Tomasová Studýnková, J.; Chura, R.; Gullick, N.; Salerno, R.; Gordon, P.; Vencovský, J.; Lundberg, I.E.
Abstract : Background: Polymyositis (PM) and dermatomyositis (DM) are chronic inflammatory diseases primarily affecting skeletal muscle leading to muscle weakness. T cells are likely to have a role in the disease process indicated by the predominance of T cells in the inflammatory infiltrates found in affected muscle, and further supported by the associations with certain HLA class II alleles. The role of T cells may be direct as mediators of muscle fiber necrosis and as producers of inflammatory molecules that may have a negative effect on muscle fiber contractility. Objectives: To assess the clinical efficacy of Abatacept, an agent blocking T cell co-stimulation, on disease activity in adult DM and PM patients in a trial with randomized treatment delayed-start design. Methods: DM and PM patients with persisting signs of inflammatory active disease after treatment with glucocorticoids and ≥1 immunomodulating drug for ≥3 months were randomized to receive either immediate active treatment with Abatacept intravenous (10 mg/kg) infusions or a delayed start after 3 months. The primary endpoint was the number of responders, defined as improved according to the International Myositis Assessment and Clinical Studies (IMACS) Group definition of improvement (DOI), after treatment for 6 months. The secondary endpoint included the number of responders in the delayed onset arm compared to the active treatment arm at 3 months, and the efficacy after 6 months treatment on the individual components of the IMACS core set measures for the disease activity, and health-related quality of life assessed by SF-36. Results: Among 20 randomized patients (9 DM, 11 PM; 13 female, 7 male), 17 were included in the analyses and 8 (47%) achieved the DOI after 6 months of active treatment. No differences between DM and PM, or female and male patients could be seen. At 3 months after study start, 5 of the 10 (50%) patients in the active treatment arm were responders achieving the DOI compared to only 1 of the 7 (14%) patients in the delayed onset arm. After active treatment for 6 months (n=17), significant improvement was seen in muscle strength, assessed by the manual muscle test (MMT)-8, from (median) 70 to 73 (p=0.0082), in gastrointestinal disease activity from 3 to 0 (p=0.0156), and in muscle disease activity from 18 to 10 (p=0.0133). SF-36 physical was significantly improved from median 31 at start to 36 at end of treatment (p=0.0054). There were 36 adverse events (AE) reported. Eight AE were judged as related to the drug, of which 4 were mild and 4 were moderate. These included infections, flank pain and dizziness. There were 3 serious AE, none of which was related to the drug. These included hospitalization due to fracture, worsening in muscle weakness and reconstructive surgery. Conclusions: In this pilot study, treatment of PM and DM patients with Abatacept resulted in improved muscle performance and health-related quality of life in half of the patients, and warrants further investigation. Acknowledgements: This research received funding support from Bristol-Myers Squibb. Disclosure of Interest: A. Tjärnlund: None declared, M. Dastmalchi: None declared, H. Mann: None declared, J. Tomasová Studýnková: None declared, R. Chura: None declared, N. Gullick: None declared, R. Salerno: None declared, P. Gordon Paid instructor for: Bristol-Myers Squibb, J. Vencovský Consultant for: Medimmune, Servier, Novartis, I. Lundberg Consultant for: Novartis, Servier, Astra-Zeneca och Bristol-Myers Squibb